2019
DOI: 10.1371/journal.pmed.1002779
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for HIV testing services among men who have sex with men in the UK: A discrete choice experiment

Abstract: Background In the UK, approximately 4,200 men who have sex with men (MSM) are living with HIV but remain undiagnosed. Maximising the number of high-risk people testing for HIV is key to ensuring prompt treatment and preventing onward infection. This study assessed how different HIV test characteristics affect the choice of testing option, including remote testing (HIV self-testing or HIV self-sampling), in the UK, a country with universal access to healthcare. Methods and findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 36 publications
2
35
1
Order By: Relevance
“…Likewise, the fact that those not meeting current testing recommendations (last test > 12 months ago) and those with lower number of previous tests also presented higher probabilities of reporting that HIV-ST would become their exclusive testing option, could suggest that these individuals are not totally comfortable with existing testing options and could switch to remote testing options. The increased probabilities of reporting that HIV-ST would become their exclusive option in higher risk participants, is in line with a UK based study that concluded that the existence of remote testing could increase testing frequency among a small group of especially at risk MSM who favored characteristics of remote testing better than those from healthcare settings [29].…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, the fact that those not meeting current testing recommendations (last test > 12 months ago) and those with lower number of previous tests also presented higher probabilities of reporting that HIV-ST would become their exclusive testing option, could suggest that these individuals are not totally comfortable with existing testing options and could switch to remote testing options. The increased probabilities of reporting that HIV-ST would become their exclusive option in higher risk participants, is in line with a UK based study that concluded that the existence of remote testing could increase testing frequency among a small group of especially at risk MSM who favored characteristics of remote testing better than those from healthcare settings [29].…”
Section: Discussionsupporting
confidence: 74%
“…Lack of testing may be attributable to structural barriers to obtaining an HIV test (e.g. clinics being difficult to access because of time constraints or capacity issues or distance); lack of knowledge about how to obtain a test; low perceived risk of HIV infection and individual psycho-social issues, including potential fear of the result, fear of needles or medical procedures, and issues around disclosure of homosexual activity and perceived stigma [15,17,27,28]. Individuals enrolled in this cohort in the knowledge that they would participate in an RCT of HIVST.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 studies that employed DCE, several base statistical models were reported, including conditional logit (4, 14%) [27][28][29][30], multinomial logit (5, 18%) [31][32][33][34][35][36], ordinary least-squares regression (2, 7%) [37,38], and logistic regression (1) [39]. Three (11%) reported relative impor-tance scores [32,40,41].…”
Section: Dcementioning
confidence: 99%
“…Several studies also conducted mixed-logit (8, 29%) [33,34,[42][43][44][45][46][47], nested-logit (3, 11%) [35,36,48], or random parameters logit (7, 25%) [32,35,[49][50][51][52][53] (some studies reported more than one model). Most of the DCE studies (24/28, 86%) further measured preference heterogeneity using stratification/subgroup analyses and/or interaction terms (17, 61%), or latent class analysis (6, 21%) [29,33,40,46,51,52]. One study used a blocked design with two different versions of the DCE for the two a priori sub-groups (past HIV testers vs non-testers) [ 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2010 2011 2012 2013 2014 2015 2016 2017 2018 2019 [24,86,88,91] were also employed, as well as types of regression (linear [92,93], count [94], log binomial [95], ordinary least squares [96], and logit link [97]).…”
Section: Dcementioning
confidence: 99%